Rock Inhibitor Y-27632 Enables Feeder-Free, Unlimited Expansion of Sus scrofa domesticus Swine Airway Stem Cells to Facilitate Respiratory Research. (23rd November 2019) - Dale, Tina P.; Borg D'anastasi, Emily; Haris, Mohammed; Forsyth, Nicholas R.
Abstract : Current limitations in the efficacy of treatments for chronic respiratory disorders position them as prospective regenerative medicine therapeutic targets. A substantial barrier to these ambitions is that research requires large numbers of cells whose acquisition is hindered by the limited availability of human tissue samples leading to an overreliance on physiologically dissimilar rodents. The development of cell culture strategies for airway cells from large mammals will more effectively support the transition from basic research to clinical therapy. Using readily available porcine lungs, we isolated conducting airway tissue and subsequently a large number of porcine airway epithelial cells (pAECs) using a digestion and mechanical scraping technique. Cells were cultured in a variety of culture media formulations, both foetal bovine serum-containing and serum-free media, in air (21%) and physiological (2%) oxygen tension and in the presence and absence of Rho kinase inhibitor Y-27362 (RI). Cell number at isolation and subsequent population doublings were determined; cells were characterised during culture and following differentiation by immunofluorescence, histology, and IL-8 ELISA. Cells were positive for epithelial markers (pan-cytokeratin and E-cadherin) and negative for fibroblastic markers (vimentin and smooth muscle actin). Supplementation of cultures with Y-27632 allowed for unlimited expansion whilst sustaining an epithelial phenotype. Early passage pAECs readily produced differentiated air-liquid interface (ALI) cultures with a capacity for mucociliary differentiation retained after substantial expansion, strongly modulated by the culture condition applied. Primary pAECs will be a useful tool to further respiratory-oriented research whilst RI-expanded pAECs are a promising tool, particularly with further optimisation of culture conditions.